AVALIAÇÃO COMPARATIVA DE DOSAGEM DO MARCADOR TUMORAL CA 15-3 EM CADELAS (Canis lupus familiaris) HÍGIDAS E COM NEOPLASIA MAMÁRIA - ROBERTO, GABRIELA BASILIO (2016)
The CA 15-3 antigen is a protein present in the serum, used to monitoring women with breast cancer, mainly in metastatic disease detection. The objectives of this study were to evaluate the effectiveness and feasibility of using the CA 15-3 tumor marker in dogs, comparing the marker values between dogs with and without breast cancer, estimating changes in marker values after mastectomy, and their correlation between the histological types. In this study, the serum quantification of tumor marker CA 15-3 (electrochemiluminescence test) was made in twenty intact healthy dogs (control group) and twenty bitches with mammary neoplasia (patient group), animals with cancer had the content of the tracer performed before and 10 days after mastectomy. Also histopathology of tumors for subsequent comparison of the data were performed. The values of the marker in the control group were an average of 0.19 + 0.39 U/mL; pre-mastectomy group 1.56 + 0.39 U/mL and post-mastectomy 0.66 + 0.27 U/mL. The statistic was performed by comparison between groups pre and post-mastectomy and the control group comparisons with the group pre and post-mastectomy with statistical significance p < 0.005 in both tests . Thus, there is a difference in marker values before and after the surgical removal of the neoplasia, indicating a significant role in post mastectomy individual control. But there is much variation results in the different existing methods, and there is still a standard reference values for each method, more research is needed on the use of markers.